2016
DOI: 10.1016/j.ajpath.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of CD206+ M2 Macrophages Ameliorates Antibody-Mediated Glomerulonephritis in Mice

Abstract: Macrophages are multifunctional immune cells that may either drive or modulate disease pathogenesis, depending on the activated phenotype. In this study, we investigated the protective effects of CD206 M2 macrophages against nephrotoxic serum nephritis in mice. We found that these immunosuppressive macrophages, derived from bone marrow and stimulated with IL-4/IL-13 [CD206 M2 bone marrow-derived macrophages (M2BMMs)], protected against renal injury, decreased proteinuria, and diminished the infiltration of CD6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…A previous study demonstrated that the amelioration of kidney injury in NTN is accompanied by an increase in the percentage of CD4 þ FoxP3 þ regulatory T cells in the KLN following transfusion of immunoregulatory CD206 þ M2 macrophages. 22 However, our study is the first to focus specifically on the association between the proinflammatory activity of FRCs in the KLN and kidney damage in crescentic GN.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study demonstrated that the amelioration of kidney injury in NTN is accompanied by an increase in the percentage of CD4 þ FoxP3 þ regulatory T cells in the KLN following transfusion of immunoregulatory CD206 þ M2 macrophages. 22 However, our study is the first to focus specifically on the association between the proinflammatory activity of FRCs in the KLN and kidney damage in crescentic GN.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, augmenting M1 macrophage differentiation renders multiple organs including the kidney more susceptible to damage, whereas transfer of CD206 + M2 macrophages attenuates glomerular injury during NTN. 19 To further investigate the effects of KLF4 on renal macrophage polarization, infiltrating CD11b + Ly6C hi inflammatory macrophages were sorted from kidneys of KLF4 MKO mice and WTs. Among the proinflammatory M1 cytokines, only TNFa in sorted CD11b + Ly6C hi was significantly increased, whereas levels of M2 markers were not altered in KLF4deficient renal macrophages.…”
Section: Augmented Renal Fibrosis and Necroptosis In Klf4 Mko Mice Ismentioning
confidence: 99%
“…The above PRR-targeting agents primarily inhibit inflammation and decrease M1 macrophage polarization. Some agents that directly target macrophages and macrophage polarization, for example, injection of genetically overexpressed IL-4 macrophages [ 91 ] or transfusion of IL-4/IL-13-differentiated bone-marrow macrophages [ 92 ] have shown a consequent M2 macrophage phenotype and reduction of the degree of renal glomerular inflammation and injury in rodents with nephrotoxic nephritis. Curcumin, a glucose metabolic homeostasis modulator, suppresses the M1 response while promoting an M2 response that enhances macrophage-mediated phagocytosis [ 93 ], and could draw attention for potential application in CKD.…”
Section: Introductionmentioning
confidence: 99%